2021
DOI: 10.3389/fdmed.2021.678477
|View full text |Cite
|
Sign up to set email alerts
|

A Need for Updating the Research Agenda for Cleft Lip and Palate and Extending the Cleft Team Model to Dental Medicine

Abstract: Care for individuals born with cleft lip and palate is done by a team approach, including dental medicine. However, oral health is not integrated in other situations that affect overall health. This perspective essay makes the case for a universal team approach, having dental medicine integrated regardless of the overall health issue, much like how cleft lip and palate is managed. Furthermore, future research agenda on the etiology of cleft lip and palate in particular will need to be adjusted for a major road… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In a recent study, the practitioners wished to have personal information to understand the patient's life situation to plan and implement appropriate health promotion activities . [31] A study done by Dao et al [23] found that most of the participants felt a lack of facilities including equipment to treat these patients. Therefore, similar to other studies , [23][24][25]32] even in the current survey it was presumed that the majority of dentists wished to have or attend additional training in the form of a hands-on workshop or an audio-visual lecture to provide more insights about the PSNAM.…”
Section: Figures 1-10: the Participants Responses To The Questionnair...mentioning
confidence: 99%
“…In a recent study, the practitioners wished to have personal information to understand the patient's life situation to plan and implement appropriate health promotion activities . [31] A study done by Dao et al [23] found that most of the participants felt a lack of facilities including equipment to treat these patients. Therefore, similar to other studies , [23][24][25]32] even in the current survey it was presumed that the majority of dentists wished to have or attend additional training in the form of a hands-on workshop or an audio-visual lecture to provide more insights about the PSNAM.…”
Section: Figures 1-10: the Participants Responses To The Questionnair...mentioning
confidence: 99%